Mastering Ansible - Fourth Edition - Freeman, James; Keating, Jesse (Packt Publishing, 2021)
Design, develop, and solve real-world automation and orchestration problems by unlocking Ansible's automation capabilities Key Features Completely revised and updated for Ansible 4.0 and beyond Tackle complex automation challenges with the newly added features in Ansible Learn about the rapidly expanding field of network automation using Ansible, with the help of practical examples for configuring network devices Book Description Ansible is a modern, YAML-based automation tool (built on top of Python, one of the world's most popular programming languages) with a massive and ever-growing user base. Its popularity and Python underpinnings make it essential learning for all in the DevOps space. This fourth edition of Mastering Ansible provides complete coverage of Ansible automation, from the design and architecture of the tool and basic automation with playbooks to writing and debugging your own Python-based extensions. You'll learn how to build automation workflows with Ansible's extensive built-in library of collections, modules, and plugins. You'll then look at extending the modules and plugins with Python-based code and even build your own collections - ultimately learning how to give back to the Ansible community. By the end of this Ansible book, you'll be confident in all aspects of Ansible automation, from the fundamentals of playbook design to getting under the hood and extending and adapting Ansible to solve new automation challenges. What you will learn Gain an in-depth understanding of how Ansible works under the hood Get to grips with Ansible collections and how they are changing and shaping the future of Ansible Fully automate the Ansible playbook executions with encrypted data Use blocks to construct failure recovery or cleanup Explore the playbook debugger and Ansible console Troubleshoot unexpected behavior effectively Work with cloud infrastructure providers and container systems Who this book is for If you are an Ansible developer or operator who has a detailed understanding of its core elements and applications but are now looking to enhance your skills in applying automation using Ansible, this book is for you. Prior experience working with core system administration tasks on Linux and basic familiarity with concepts such as cloud computing, containers, network devices, and fundamentals of a high-level programming language will help you make the most of this book.